Flipped Classroom: Thai Language Learning Management to Develop Learners in the Next Normal Era - Kongrat, Chedtharat (Ratchaphruek Journal, 2022)
The flipped classroom is a learning management concept for the new normal era where information technology plays an important role in human life. Due to the Coronavirus Disease 2019 (COVID-19) epidemic situation, it is impossible to teach normally. The flipped classroom is, therefore, a learning model that changing the traditional paradigm to a new paradigm which is suitable and in line with the current situation. This new paradigm aims to urge learners to seek knowledge on their own by using digital technology as a tool to support the learning process. For Thai Language classes, learning management should change from educating to enabling learning. Students are encouraged to change the way they learn and present their work in their classrooms by studying the content before they go to the class using digital learning platforms. Then, students apply what they have learned from pre-class activities to in-class activities as well as exchange ideas with their classmates. Teachers are responsible for coaching, observing their learning behaviors, and assessing the results. The assessed results must be used to improve the student's learning process. In addition, content is reviewed in the flipped classroom, or the knowledge gained is used to create a post-learning task. In summary, the flipped classroom is a model of learning management that develops learners in terms of knowledge, skills, and attributes in Thai Language subject. It empowers students to be competent for learning in the 21st century and ready to learn in the next normal era effectively.